Academic Freedom and the Humanities: some current challenges - Higgins, John (Critical Studies in Teaching and Learning, 2023)
This article presents some of the current challenges facing academic freedom and the humanities in South Africa as well as across the world. It focuses first on the shifting fortunes of academic freedom in South Africa, contrasting the pride of place given to it in the pre-1994 social imaginary with its current undermining in higher education policy.  It further examines how this undermining is related to a general trend in a global higher education policy which privileges STEM disciplines, and argues that a fuller understanding of the contribution of the NAIL disciplines to the public good is essential to help counter current challenges.